Analisa Risiko Kejadian Hipertensi Pada Masyarakat Usia Produktif di Wilayah Kerja Puskesmas Pancoran Mas Depok Tahun 2022: Analysis of the Risk of Hypertension in People of Productive Age in the Working Area of the Pancoran Mas Health Center, Depok in 2022 - Demiyati, Cici; Sitepu, Kesia Aprilia br; Marliana, Adelia; Nurmalia; Kabelen, Vinsensius Yosef (MPI Press, 2023)
Background: Hypertension is a chronic disease characterized by high blood pressure. This elevation forces the heart to work harder than usual to pump blood through the blood vessels. According to World Health Organization (WHO) data in 2015, around 972 million people or 26.4% suffer from hypertension, and this figure is estimated to increase to 29.2% by 2025. Objective: To analyze the risk of hypertension incidence in the productive age group in the working area of Pancoran Mas Health Center, Depok. Method: This research used a quantitative method conducted online through Google Forms (questionnaire) observation. Data processing was carried out from secondary data (Depok city health profile 2019 and other supporting journals) and primary data (questionnaire - Google Forms) using Microsoft Excel. Results: The results of this research indicate that genetic factors, behavioral factors, and healthcare service factors contribute to the risk of hypertension in the working area of Pancoran Mas Health Center, Depok. The coverage of informants experiencing hypertension is 12 (13.3%) out of 14 (15.5%) who have a genetic disease risk. The factors contributing to hypertension in the working area of Pancoran Mas Health Center, Depok, include a lack of physical activity by 69 individuals out of 90 respondents and irregular health check-ups by 41 individuals out of 90 respondents. Conclusion: Based on the occurrence of hypertension in the Depok city area, it is caused by genetic factors (family lineage), behavior (lack of regular physical activity), and routine health check-ups (insufficient regular health check-ups).